Relationship between public administrative reform and scientific and technological management reform in Vietnam - Ai Thi, Dao Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Over past many years, scientific and technological (S&T) management in Viet Nam encountered a lot of difficulties due to lack of a public administration platform to promote a maximum use of S&T resources for the construction and development of the country. Vietnam has already undergone two phases of the country’s administrative reform strategy (1991-2001, 2001-2010), and is now implementing phase 3 (2011-2020). It was observed that though S&T was present in all areas of life, S&T management had almost been separated from the general trend of the country’s administrative reform. Achievements of modern science and technology had not been properly utilized by the administrative reform itself, therefore it was difficult for it to support effectively the state management of science and technology. So, in the process of administrative reform period 2011-2020, if the public administrative reform is not associated with the management reform of individual sectors/areas towards achieving a synchronized reform effort it is really hard to talk about the effectiveness of public administrative reform as well as an effective S&T management. The purpose of this paper is to show the relationship between different aspects of administrative reform and their connection with the S&T management reform, including institutional reform, organizational structure reform, empowerment of public servants, reform of public financial management related to S&T management.